EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP SISWA - Unedo Samosir; Katrina Samosir (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is an experimental research which aim is to know whether Realistic Mathematics Education approach is effective on ability of students’ mathematical concept understanding or not. The population in this research is all the students of class VIII SMP Swasta Bakti Mulia Onanrunggu. The sample is the students of class VIII-A as experimental group and the students of class VIII-B as control group. The instruments which are used consist of the ability of mathematical concept understanding test in α = 5% and df = 28 + 30 - 2 = 56, teacher’s observation notes, and student’s observation notes. Data analysis is done with t test, minimal mastery criteria , classroom activity and student response . The results of this research proves that Realistic Mathematics Education approach is effective on the ability of students’ mathematical concept understanding within score of t count is greater than t table . Classical mastery criteria accomplished by (85,7%) within individual mastery reach into 75,67. Class activity falls into the active category (76,7%), and student responses fall into the positive category (91,06%).